Hubungan Personal Hygiene Terhadap Keberadaan Jamur Candida Albicans Penyebab Gejala Keputihan Pada Urin Mahasiswi di Perguruan Tinggi XXXX Tahun 2024 - Linda Utami; Hamril Dani; Warsinah Warsinah; Nur Afni Sulastina; Yurika Kirana (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research generally aims to determine "The relationship between personal hygiene and the presence of the fungus Candida Albicans which causes symptoms of vaginal discharge in the urine of female students at Xxxx College in 2024". Meanwhile, specifically, this research aims to: (1) Find out the frequency distribution of Personal Hygiene for Female Students at Xxxx College in 2024. (2) Find out the frequency distribution of the Candida Albicans fungus that causes vaginal discharge symptoms in the urine of Female Students at Xxxx College in 2024. (3) Know it Frequency distribution of the Candida Albicans fungus that causes symptoms of vaginal discharge in the urine of female students at Xxxx College in 2024 based on age. (4) Whether or not there is a relationship between personal hygiene and the presence of the fungus Candida Albicans which causes symptoms of vaginal discharge in the urine of female students at Xxxx College in 2024. The research design used is descriptive. Based on this research, it was found that: (1) Based on 20 female students with good personal hygiene, there were 11 (55%) female students who were positive for Candida albicans fungus and 9 (45%) female students who were negative for Candida albicans fungus. Meanwhile, of the 14 students with poor personal hygiene, 9 (64.29%) students were positive for Candida albicans fungus and 5 (35.71%) students were negative for Candida albicans fungus. (2) Based on the 34 female student urine samples examined, the results showed that 20 samples (58.82%) were positive for Candida albicans fungus and 14 samples (41.18%) did not find Candida albicans fungus. (3) Based on 34 urine samples of female students who were examined in their middle teens (15-17 years), the results showed that 1 sample (9.09%) was positive for Candida albicans fungus and 10 samples (90.91%) were negative for Candida albicans fungus. Meanwhile, in late adolescence (aged 18-22 years), 19 samples (82.61%) had positive urine results containing Candida albicans fungus and 4 samples (17.39%) had negative urine results and no Candida albicans fungus was found. (4) Based on analysis using the Chi square test, the statistical test results show that there is a relationship between personal hygiene and the presence of the fungus Candida Albicans which causes vaginal discharge symptoms in the urine of female students at Xxxx College in 2024 with a value of P = 0.021 < α = 0.05.